2016
DOI: 10.17159/0379-4350/2016/v69a13
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide/zinc oxide nanocomposite: A superior adsorbent for removal of methylene blue - statistical analysis by response surface methodology (RSM)

Abstract: The graphene oxide was prepared from graphite powder by a modified Hummers method. 29 Briefly, 1 g graphite powder, 6 g KMnO 4 and 1 g NaNO 3 were mixed with 46 mL concentrated sulphuric acid (97 %). The mixture was stirred for 3 h within an ice-bath. After having been removed from the ice-bath, 280 mL deionized water was added and stirred at room temperature for 2 h. Then the sample was stirred at 89°C for 2 h, followed by 6 mL H 2 O 2 which was added dropwise until the colour of the solution turned from dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…After ZnS deposition, the dips tend to shift towards a lower energy (enlarged part of the IR spectra in Figure 5b, marked by dotted magenta frame). A weak and broad band appearing at around 484 cm -1 may originate from the Zn-O stretching vibration [33,36,37,45]. In Figure 5, the IR spectrum of the studied samples are presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After ZnS deposition, the dips tend to shift towards a lower energy (enlarged part of the IR spectra in Figure 5b, marked by dotted magenta frame). A weak and broad band appearing at around 484 cm -1 may originate from the Zn-O stretching vibration [33,36,37,45]. In Figure 5, the IR spectrum of the studied samples are presented.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic peaks of IR spectra for 1,5-pentanedithiol can be attributed from each as-deposited Zn-S films on AAO indicating MLD type growth [34,35]. The strongest dips at 2927 and 2851 cm −1 were ascribed before to the CH 2 asymmetric (v a (CH 2 )) and symmetric (v s (CH 2 )) stretching vibrational modes, respectively [29,30,[36][37][38]. These dips are also the most intensive ones in the IR spectrum of pure PDT [34,35] and can thus be regarded as chemical fingerprints of this compound.…”
Section: Resultsmentioning
confidence: 99%
“…8 was undertaken in a stepwise fashion, with the ZnONPs adsorbed onto the surface of the GO, resulting in an adsorption energy of the ZnONP/GO complex (see Table 2 ) stabilized at − 13.852 kcal/mol. The adsorption performance and sensitivity of ZnONPs have been recently reported in literature 113 , 114 . As much as this study attempted to mimic experimental conditions, it is evident in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In two contemporary publications Hosseini et al 151,152 have reported the preparation of a GO/ZnO composite by the solution method and have applied the same for the removal of a dye (MB) from water following adsorptive and photocatalytic techniques respectively. In the first publication 151 adsorption efficiency was monitored and nanocomposites were observed to exhibit the highest (97%) efficiency of removal of MB at 5 ppm concentration under optimum conditions: pH 6, adsorption time 8.5 min, and adsorbent dosage 0.02 g. But under the same conditions ZnO, GO, pure carbon nanotube (CNT) and ZnO/CNT exhibit 5.165%, 78.82%, 95.42% and 17.13% removal of MB respectively. Therefore, prepared GO/ZnO exhibits the highest dye removal efficiency and it can be used for removal of industrial dyes from waste water via adsorption.…”
Section: Go–metal Oxide (Mo) Based Nanocompositesmentioning
confidence: 99%